KONDISI MAKROEKONOMI SEBAGAI FAKTOR YANG MEMPENGARUHI NERACA TRANSAKSI BERJALAN PERIODE 1999-2016 - Erric Wijaya (Jurusan Akuntansi Politeknik Negeri Bandung, 2019)
This study discusses the current account and itsinfluencing factors. The factors influencing the current account are macroeconomic factors, including national income (GDP), inflation, interest rate (SBI), and exchange rate.The period of this study starts from 1999 - 2016 using annual data. This study looks at the short-term and long-term effects of macroeconomic factors that affect the current account balance. The research model of this study was using cointegration test and Error Correction Model (ECM).The results showed that in the long run, the macroeconomic variables of national income (GDP) and inflation significantly influenced the current account balance. While in the short term, macroeconomic variables inflation and exchange rate significantly influenced the current account balance. Thusit can be concluded that, the inflation variable is the main macroeconomic variable that influenced the current account balance in the long term and in the short term. Keywords: current account, national income, SBI, inflation, exchange rate